Outcome of the entomological monitoring for Crimean-Congo haemorrhagic fever virus in the western and southern regions of Kazakhstan in 2021–2022 - Nurmakhanov, T.; Tukhanova, N.; Sayakova, Z.; Sadovskaya, V.; Shevtsov, A.; Tokmurziyeva, G.; Turebekov, N. (Frontiers in Epidemiology, 2024)
The natural foci of Crimean-Congo haemorrhagic fever (CCHF) in Kazakhstan are geographically located in the southern regions of the country (Kyzylorda, Turkestan and Zhambyl regions), where the infection of ticks with the CCHF virus predominantly reside, tick species composition and the number of vectors are monitored annually. The objective of our research was to investigate the genetic variants of the CCHF virus in the southern endemic regions, as well as to monitor the spread of the CCHF virus in the western regions of the country (Aktobe, Atyrau and Mangystau regions). In total, 974 (216 pools) ticks from the western regions and 3527 (583 pools) ticks from the southern regions collected during 2021-2022 were investigated. The presence of CCHF virus was detected by real-time reverse transcription PCR (qRT-PCR) in 1 pool out of 799 pools (0.12%) with Hyalomma scupense ticks captured in the CCHF-endemic Kyzylorda region. In the western regions, CCHF virus was not detected in ticks. The sequencing of incomplete fragments ofthe S, M and L segments ofthe CCHF virus in the detected virus was identified as genotype Asia - I. Phylogenetic analysis showed that the isolate obtained in this study is grouped with the isolate from a patient with CCHF, which we reported in 2015 (KX129738 Genbank). Our findings highlight the importance of including sequencing in the annual monitoring system for better understanding the evolution of the CCHF virus in the study areas of our country.